2012
DOI: 10.1292/jvms.12-0142
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Metals in the Liver and Kidneys of Cattle from Agricultural Areas in Lusaka, Zambia

Abstract: ABSTRACT. Intensive agricultural practices are recognized as significant sources of metal pollution in soils and pasture. This study investigated metal contamination in cattle offal from an agricultural area in Zambia, where inorganic fertilizers, agricultural lime, and pesticides are routinely applied. The highest median values (mg/kg, wet weight) of Cu (40.9), Zn (35.2), Cr (1.35) and Ni (0.594) were recorded in the liver, whereas the highest median values of Pb (0.061) and Cd (0.049) were found in kidneys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Maize, wheat rice, sorghum, and cassava are the main gain crops. Manure and mineral fertilizers, agricultural lime, and pesticides are routinely applied in the agriculture, which had been recognized as significant sources of metal pollution in Africa . Secondly, domestic and industrial discharges from Nakuru town (a population of approximately 212 000 inhabitants) enter the lake through surface inflows, which may be an important source of heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…Maize, wheat rice, sorghum, and cassava are the main gain crops. Manure and mineral fertilizers, agricultural lime, and pesticides are routinely applied in the agriculture, which had been recognized as significant sources of metal pollution in Africa . Secondly, domestic and industrial discharges from Nakuru town (a population of approximately 212 000 inhabitants) enter the lake through surface inflows, which may be an important source of heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the levels of zinc and chromium (dry and fresh weights, fw) in this study were much higher than those reported by others, a further indication of substantial contamination of the Nigerian environment by zinc and chromium. [32][33][34][35] Most zinc enters the environment as the result of mining, zinc purification, lead and cadmium ores, steel production, coal burning, and waste burning. Chromium sources may come from waste effluents discharged from textile, pigment, leather tanning, and electroplating industries, and/or incineration of municipal refuse and sewage sludge.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the occurrence of huge mine generated wastelands in Southern-Central Africa (Venkateswarlu et al 2016), little information is available, particularly in Zambia, regarding the physicochemical characteristics as well as the distribution and concentration of heavy metals across these wastelands. Previous studies have mainly focused on heavy metal accumulation and its biological impact (Yabe et al 2011(Yabe et al , 2012M'kandawire et al 2012;Kapungwe 2013;Nakayama et al 2013) and heavy metal accumulation in soils and sediments (Ikenaka et al 2010).…”
Section: Introductionmentioning
confidence: 99%